Sub-Tenon Injections of Triamcinolone Acetonide Had Limited Effect on Cystoid Macular Edema Secondary to Nanoparticle Albumin-Bound-Paclitaxel (Abraxane) - Naoki Matsuoka; Hiruma Hasebe; Tetsuji Mayama; Takeo Fukuchi (Case Reports in Ophthalmological Medicine)
Purpose. To report the first case of cystoid macular edema (CME) induced by nanoparticle albumin-bound- (nab-) paclitaxel treated with sub-Tenon injections of triamcinolone acetonide (STTA) with detailed long-term follow-up. Case. A 39-year-old Japanese woman with breast cancer presents with decreased vision in both eyes while receiving nab-paclitaxel. Two STTA treatments were administered for persistent CME in her right eye. Central retinal thickness (CRT) of the treated eye decreased after the first STTA, but there was no change after the second STTA. CRT of the other eye and bilateral visual acuity (VA) showed no change after each treatment. However, this patient experienced gradual recovery of visual function after nab-paclitaxel treatment was completed, 3 months after the second STTA. Improvements in VA and CRT did not overlap in time. Moreover, there was a big improvement time lag in VA between the eyes. Conclusion. Cessation of nab-paclitaxel could lead to resolution of CME more than STTA, although STTA had some effect. Since nab-paclitaxel has been recently approved for treating more types of malignancies, the number of the patients with this CME is expected to increase in the near future. Patients and physicians should understand this side effect and prepare for other treatment options.